Diplomasi Kerjasama Turki Utsmani dengan Aceh Darussalam pada Abad ke-16 Masehi: Tinjauan Historis dalam Perspektif Hubungan Internasional Islam - Soviani, Aisa (Medan Resource Center, 2025)
This study examines the diplomatic relations between the Ottoman Empire and the Sultanate of Aceh Darussalam in the 16th century CE. Employing historical research methods comprising heuristic (source collection), verification, interpretation, and historiography, this research relies on primary sources comprising archival documents and manuscripts from the Topkapi Palace in Istanbul, alongside secondary sources from various historical journals and books. The findings reveal that: (1) diplomatic relations between the two sultanates were formally established during the reign of Sultan Alauddin Riayat Syah Al-Qahhar in Aceh and Sultan Suleiman Al-Kanuni in the Ottoman Empire, marked by the arrival of the Acehnese envoy in Istanbul in 1547 CE; (2) supporting factors for cooperation included Islamic solidarity (ukhuwah islamiyah), shared interests in resisting Portuguese colonial expansion, and common trade routes across the Indian Ocean and the Strait of Malacca; (3) forms of cooperation encompassed military affairs (deployment of troops, cannons, and artillery specialists), trade and economics (pepper and spices), politics (sovereignty recognition and diplomatic representation), as well as religious da'wah (Islamic proselytization). This research affirms that the Ottoman–Aceh Darussalam relationship represents a concrete example of transcontinental Islamic diplomacy grounded in shared doctrinal values and mutual strategic interests in countering European colonial hegemony in the Southeast Asian maritime sphere.